Generative artificial intelligence in university teaching - application case (Costos y Gestión, 2025)
Given the emergence of generative artificial intelligence as a new “black swan” based on the exponential adoption of OpenAI's GPT3.5, many alarm bells were raised in the university environment about its misuse, particularly to “copy” itself during evaluation moments. Like any technological evolution, there is always the possibility of standing on the opposite vantage point, purposefully seeking the benefits that it can bring to the collaborative learning process. The presentation aims to be a trigger for a necessary debate for the creation of a new zeitgeist, and for this we share two experiences of use at the University of Buenos Aires, including the results achieved: At evaluation time, both to raise awareness of the difference between text generation tools and the generation of epistemological knowledge, and to stimulate critical questioning. In the study of a topic prior to being discussed in class, to motivate bringing out and self-management of the learning process.
Keywords: generative artificial intelligence; GPT; didactics; application case; elicit